Pengaruh Service Innovation Dan Service Quality Terhadap Costumer Satisfaction (Studi Kasus Pada Balai Pelatihan Vokasi Dan Produktivitas Ternate) - Akram Pora; Ida Hidayanti; Sulfi Abdul Haji (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the effect of Service Innovation and Service Quality on Customer Satisfaction (Case Study at the Vocational Training Center and Ternate Productivity). This research is a quantitative research. The population in the study were students from the Ternate Vocational and Productivity Training Center. The number of research samples is 122 respondents. The data analysis technique used in this study was multiple linear regression analysis using Smart Partial Least Square (PLS) version 4.0 as a statistical test tool. The results of this study indicate that: (1) Service innovation has a positive and significant effect on customer satisfaction at the Ternate Vocational and Productivity Training Center; and (2) Service quality has a positive and significant effect on customer satisfaction at the Ternate Vocational and Productivity Training Center.